Foreign Ownership and the Theory of Trade and Welfare - Brecher, Richard A.; Bhagwati, Jagdish N. (Journal of Political Economy, 1981)
Some standard topics in the theory of international trade are reconsidered in this paper by distinguishing between national and aggregate income when fixed supplies of foreign inputs are present within the home country. Under conditions that would ensure a national welfare gain if foreign ownership were absent, international transfer, economic growth, or tariff policy might cause a national welfare loss in the presence of foreign ownership. The techniques developed could be applied to other domestic distinctions (such as those based on race, sex, age, or ethnicity) and to the theory of customs unions in a three-country world.